Answer:
225
Step-by-step explanation:
The sum of this series is given by the formula:
![S_n=\frac{n}{2}[2a+(n-1)d]](https://tex.z-dn.net/?f=S_n%3D%5Cfrac%7Bn%7D%7B2%7D%5B2a%2B%28n-1%29d%5D)
Where
S_n is the sum
a is the first term (we get this by plugging in n = 1 into "2n-1", we have 2(1) - 1 = 1)
n is the number of terms (the sum is defined for n = 1 to n = 15, so 15 terms)
d is the common different (the difference is successive terms. Here, 2nd term would be 2(2) - 1 = 3, and first term was 1, so d = 3 -1 = 2)
<em>plugging in the info, we will get the sum:</em>
<em>
</em>
<em>The sum is 225</em>
-4(x-7)=36
-4x+28=36
-4x=8
x=-2
Answer:
no clue buddy sry
Step-by-step explanation:
Answer:
Incorrect.
Step-by-step explanation:
Let, the first number is x, and the second number is y. Given, the second number is 125% of the first number. So, the equation will be
y = 1.25 x
Or, y= 5/4x
Now, multiplying it with 4/5, we get, x= 4/5y
Or, x= 0.80 y
But, Brad is saying the first number must be 75% of the second number. But here we see that the first number is 80% of the second number. That's why Brad is incorrect.